2021
DOI: 10.1371/journal.pone.0246234
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quality score is positively associated with serum adiponectin level in Indonesian preschool-age children living in the urban area of Jakarta

Abstract: An unhealthy diet during childhood directly impacts the risk of developing noncommunicable diseases (NCDs) later on in life. However, well-documented information on this issue is lacking. We investigated the dietary quality of young Indonesian children and assessed the relationship to serum adiponectin levels as an early marker of NCDs. Eighty-five (44 girls and 41 boys) Indonesian preschool-age children in East Jakarta were included in this study. Dietary intake data were gathered by collecting repeated 24-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
2
0
3
Order By: Relevance
“…The HEI-2015 score obtained in this study was considered as poor diet quality (Krebs-Smith). Other studies led by Indonesian researchers also showed poor diet quality (HEI-2015 score < 50) in healthy Indonesian women and preschool-age children living in the urban area [14,15]. According to the 2020-2025 Dietary Guidelines for Americans [30], the HEI-2015 score of American citizens ranged from 51 (teenagers of 14-18 years) to 63 (elderly aged 60 or older).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEI-2015 score obtained in this study was considered as poor diet quality (Krebs-Smith). Other studies led by Indonesian researchers also showed poor diet quality (HEI-2015 score < 50) in healthy Indonesian women and preschool-age children living in the urban area [14,15]. According to the 2020-2025 Dietary Guidelines for Americans [30], the HEI-2015 score of American citizens ranged from 51 (teenagers of 14-18 years) to 63 (elderly aged 60 or older).…”
Section: Discussionmentioning
confidence: 99%
“…The HEI-2015 score ranges from 0 to 100, with a higher score representing a better diet quality (scores>80 good, 51-80 needs improvement, and <51 poor). It is noteworthy that although the HEI has not been validated in Indonesia and its implementation to measure individual diet quality is still not common, recent Indonesian studies have succeeded in obtaining valid findings using the HEI [14] [15].…”
Section: Healthy Eating Index (Hei-2015)mentioning
confidence: 99%
“…Menurut Khakpouri et al, peningkatan skor Healthy Eating Index berhubungan dengan penurunan risiko berbagai penyakit kronis atau penyakit tidak menular Khakpouri et al (2019). Penelitian yang dilakukan sebelumnya menjelaskan bahwa skor total Healthy Eating Index berkorelasi positif dengan nilai hormon adiponektin tubuh, dimana hormon adiponektin yang tinggi dapat menurunkan risiko obesitas, diabetes, inflamasi, dan penyakit kardiovaskuler Hayuningtyas et al (2021). Hal tersebut menunjukkan bahwa semakin berkualitas diet yang diterapkan oleh seseorang, maka semakin rendah risiko orang tersebut untuk mengalami berbagai penyakit.…”
Section: Pendahuluanunclassified
“…Berbagai zat tersebut dapat berhubungan dengan keseimbangan mikrobiota usus serta peningkatan adiponektin, sehingga berdampak pada penurunan sitokin proinflamasi. Adanya penurunan sitokin tersebut dapat menurunkan kondisi inflamasi dan resistensi insulin, sehingga glukosa darah akan lebih terkontrol Hayuningtyas et al (2021). Dalam penelitian ini juga didapatkan bahwa skor IGS lemak jenuh dan lemak total pada kelompok responden dengan nilai glukosa darah normal lebih tinggi dibandingkan pada kelompok yang nilai glukosa darahnya tinggi.…”
Section: Metodeunclassified
See 1 more Smart Citation